2016
DOI: 10.3354/ame01798
|View full text |Cite
|
Sign up to set email alerts
|

Molecular investigation of protistan diversity along an elevation transect of alpine lakes

Abstract: Ecological gradients are one of the main reasons for changes in biodiversity. However, whether what is known to be true for plants and animals also applies to protists in the same way is largely unknown. Along an alpine elevation gradient, including 29 freshwater lakes, we investigated ecological drivers of protistan diversity and community structure, as well as the explanatory value of the species−area relationship for protistan diversity using a deep-sequencing approach. We found that species richness does n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
20
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 48 publications
3
20
1
Order By: Relevance
“…In accordance with our findings, a large genetic divergence between distinct lake microbial communities has been reported in recent deep-sequencing campaigns, in particular for the rare biosphere (Filker et al 2016, Grossmann et al 2016b, Triadó-Margarit and Casamayor 2012. In particular, distribution patterns of rare taxa seem to vary widely and to deviate from the rather uniform patterns in abundant protists (Grossmann et al 2016a, Schiaffino et al 2016). This confirms recent claims that distribution patterns are almost certainly differential, with some taxa being ubiquitous whereas others are rather endemic, as proposed for instance by the moderate endemicity model.…”
Section: Eukaryotic Microbial Molecular Diversity In European Freshwasupporting
confidence: 91%
See 3 more Smart Citations
“…In accordance with our findings, a large genetic divergence between distinct lake microbial communities has been reported in recent deep-sequencing campaigns, in particular for the rare biosphere (Filker et al 2016, Grossmann et al 2016b, Triadó-Margarit and Casamayor 2012. In particular, distribution patterns of rare taxa seem to vary widely and to deviate from the rather uniform patterns in abundant protists (Grossmann et al 2016a, Schiaffino et al 2016). This confirms recent claims that distribution patterns are almost certainly differential, with some taxa being ubiquitous whereas others are rather endemic, as proposed for instance by the moderate endemicity model.…”
Section: Eukaryotic Microbial Molecular Diversity In European Freshwasupporting
confidence: 91%
“…Considerable research effort has been focused on marine diversity (Countway et al 2005,Countway et al 2007, Campo et al 2016, Lovejoy et al 2006, López-García et al 2001, Massana and Pedrós-Alió 2008, Worden et al 2006. Despite the global importance of freshwater resources and the heterogeneity of freshwater systems, their biological diversity has been comparatively neglected (Filker et al 2016, Grossmann et al 2016a, Kammerlander et al 2015, Lepère et al 2007, Taib et al 2013, Triadó-Margarit and Casamayor 2012, Slapeta et al 2005. Our study revealed a high diversity of microbial freshwater eukaryotes and a high level of regional separation.…”
Section: Eukaryotic Microbial Molecular Diversity In European Freshwamentioning
confidence: 78%
See 2 more Smart Citations
“…The sequence data analyzed in the current study was taken from [9, 10] (Additional file 1). It stems from a set of alpine Austrian lakes, which were sampled in order to study the change of lake microbial ecosystems of three different lakes over time [9] and the difference in microbiome composition over many lakes [10].…”
Section: Methodsmentioning
confidence: 99%